Numerical studies and industrial applications of the hybrid SPH-FE method. (30th April 2019) - Groenenboom, P.; Cartwright, B.; McGuckin, D.; Amoignon, O.; Mettichi, M.Z.; Gargouri, Y.; Kamoulakos, A.
Highlights: Fluid-structure interaction by SPH-FE coupling. Enhancements for the SPH method. Selected validation examples. Applications examples: ship in waves, lubrication of a gearbox, cardiovascular flow. Abstract: Over the last few decades, the Smoothed Particle Hydrodynamics (SPH) method has gained popularity as a mesh-less method to simulate fluid flows. In contrast, the finite element (FE) method remains the preferred tool to simulate structural deformation. This paper presents a coupled SPH-FE software tool useful for a large variety of dynamic fluid flow simulations and fluid-structure interaction. Several recent developments in the SPH algorithm are presented as well as a few studies demonstrating the validity in comparison to experimental data. Following a brief overview of industrial applications of the hybrid SPH-FE method, three computational studies are discussed in greater detail. These concern ships in waves, gearbox lubrication and cardiovascular flow. It is shown that the SPH-FE approach is well-suited for violent flow phenomena and fluid-structure interaction.